O papel das extensionistas de bem-estar social após a PNATER: estudo de caso de EMATER’s da regional de Lavras e Alfenas - Aguiar, Marcos Paulo Souza (2020)
With the present dissertation, entitled “The role of social welfare extension workers after PNATER: Emater’s case study from Lavras e Alfenas regional”, the objective was to discuss the role of social welfare extension workers (BES) in EMATER, analyzing its functions, intervention perspectives, use of educational / participatory methodologies and challenges faced after the National Policy for Technical Assistance and Rural Extension. To do so, a theoretical-empirical research was used, because in addition to appropriating bibliographic, documentary and electronic research, it was carried out in the field through semi-structured interviews with BES. Among the conclusive aspects of this work, the historical recognition of rural extension in Brazil and the premises established by PNATER that somehow influence the action of extension workers are evidenced as theoretical gains. Through the field research, the interviewees' demographic and professional profile was appropriated, as well as results were obtained from the objectives of such research. It is estimated that there was an expansion of knowledge about rural extension in Brazil and mainly the role of social welfare extensionist. It is hoped that this research can contribute to the role of extension worker and provide subsidies for new studies, in particular, on the contexts of intervention, territoriality and public policies for the rural population.